2011
DOI: 10.4293/108680811x13176785204409
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Warm-Up Using a Virtual Reality Simulator

Abstract: Even more experienced laparoscopic surgeons in this report became better prepared to perform a surgical procedure doing simple exercises on a virtual reality simulator before the actual procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 18 publications
0
81
1
3
Order By: Relevance
“…The nine other studies[24Ð28, 30,31,33] included in this review reported significant results in some, but not all, recorded outcome measures. All of these studies concluded overall that preoperative simulation improves surgical performance, but only two studies [25,28] (48,51) include an explanation as to why significant results were prioritised over non-significant results.…”
Section: The Warm-up Tasksmentioning
confidence: 90%
See 4 more Smart Citations
“…The nine other studies[24Ð28, 30,31,33] included in this review reported significant results in some, but not all, recorded outcome measures. All of these studies concluded overall that preoperative simulation improves surgical performance, but only two studies [25,28] (48,51) include an explanation as to why significant results were prioritised over non-significant results.…”
Section: The Warm-up Tasksmentioning
confidence: 90%
“…A further four studies were case studies, two compared a technical skills practice to no practice [30,31] and two [32,33] did not contain a control group. One RCT [34] examined the effect of mental practice prior to an operation on subsequent laparoscopic performance.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations